A thing about karate in physical culture - Piepiora, Paweł Adam; Čaplová, Petra; Cynarski, Wojciech Jan (Frontiers in Sports and Active Living, 2024)
This paper deals with karate activity in the areas of physical culture in the broad sense. It is a concise and clear approach to the topic, which aimed to conceptualise the inclusion of karate in areas of physical culture as a contemporarily attractive physical activity. Karate was described here as a combat sport, martial art, and self-defence system in the following areas of physical culture: physical education, physiotherapy, recreation, sports, and tourism. Reference here was made to physical activity focused on bunkai (circuit interpretation exercises), kata (circuit exercises), kihon (technical exercises), and kumite (combat exercises). It has been determined that practitioners’ involvement in karate culture affects their level of sense of coherence. In addition, the conditioning for using karate in physical culture to the maintenance of health was mentioned. Here, reference was made to the perceptual perspective of the bodily and mental practice of karate for health. It has been established that this can be effective by adopting only the objectives of karate as martial art. Based on the above, it was concluded that practising karate is present in all areas of physical culture as combat sport, martial art, and self-defence system, but practising karate only as martial art provides opportunities for maintenance of health.